The Utilization of Artificial Intelligence (AI) Based Media In Enhancing The Learning Process At The Elementary School Level - Annisa Nidaur Rohmah (BASICA, 2024)
This study aimed to present a literature review on the utilization of Artificial Intelligence (AI)-based media in enhancing the learning process at the elementary school level. The study used a systematic literature review method, concentrating on the theme of AI-based media in elementary education. The main sources used are writings and documents related to the use of AI-based media in learning at the elementary school level. Apart from that, this research also collects data from secondary sources such as books and academic articles that discuss the use of AI-based media in learning in general to provide a broader understanding. After data collection, data analysis was carried out to identify the use of AI-based media in learning. This analysis involved breaking down concepts and how these concepts were implemented in learning at the elementary school level. Based on the findings from the literature review, the utilization of AI-based media in elementary education has the potential to deliver a learning experience tailored to students’ needs. Moreover, AI-based media supports the implementation of game-based learning, fostering a more challenging and dynamic educational environment that actively engages students. Additionally, the use of AI-based media contributes to the development of students’ competencies. The competencies that can be enhanced include critical thinking, communication, and creativity. Therefore, implementing AI-based media in elementary school education should take into account the needs of students, which can lead to significant improvements in their competencies.